2018
DOI: 10.1159/000485591
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Acute Kidney Injury in Intensive Care Unit Patients: The Role of Tissue Inhibitor of Metalloproteinases-2 and Insulin-Like Growth Factor-Binding Protein-7 Biomarkers

Abstract: Background: Acute kidney injury (AKI) diagnosis is based on a rise in serum creatinine and/or fall in urine output. It has been shown that there are patients that fulfill AKI definition but do not have AKI, and there are also patients with evidence of renal injury who do not meet any criteria for AKI. Recently the innovative and emerging proteomic technology has enabled the identification of novel biomarkers that allow improved risk stratification. Methods: Tissue inhibitor of metalloproteinases-2 (TIMP-2), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Contrasting results regarding interventions to prevent AKI have led to disappointment regarding the use of biomarkers alone [35,36]. Nevertheless, (TIMP-2)•(IGFBP7) improved the predictive performance at ICU admission of a clinical model for AKI at any stage ( Ferrari F , submitted to Scientific Reports 2018 , [37], even if its best performance is to identify patients at risk of developing severe (stage 2–3) AKI [3840].…”
Section: Resultsmentioning
confidence: 99%
“…Contrasting results regarding interventions to prevent AKI have led to disappointment regarding the use of biomarkers alone [35,36]. Nevertheless, (TIMP-2)•(IGFBP7) improved the predictive performance at ICU admission of a clinical model for AKI at any stage ( Ferrari F , submitted to Scientific Reports 2018 , [37], even if its best performance is to identify patients at risk of developing severe (stage 2–3) AKI [3840].…”
Section: Resultsmentioning
confidence: 99%
“…Among these, surgical patients were the target population, including patients undergoing coronary artery bypass graft surgery with cardiopulmonary bypass 18 , valvular, or combined surgery with cardiopulmonary bypass 19 and no cardiac surgery 20 . Meersch 21 and Gocze 22 estimated an AUC for AKI stage 1 of 0.81 and 0.85, respectively. With an estimated cut-off of 1.1 (ng/ml) 2 /1000, Wetz and colleagues were able to discriminate between patients with and without AKI on the first postoperative day with an AUC of 0.706, albeit this study did not include high risk patients and those undergoing urgent surgery 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, Di Leo et al . evaluated the value of [TIMP-2]∙[IGFBP7] to predict AKI free days in 719 critically ill patients, estimating an optimal cut-off of 0.37 (ng/ml) 2 /1000 (AUC 0.633, specificity and sensitivity 56% and 64%, respectively), thereby demonstrating that [TIMP-2]∙[IGFBP7] captures most AKI positive cases and a high number of patients who do not develop AKI 21 .…”
Section: Discussionmentioning
confidence: 99%
“…studied a population of critically ill patients and found that the values of cell cycle arrest biomarkers were higher in transient versus persistent AKI at early hours after ICU admission. 77 Aregger et al. showed that IGFBP7 predicted mortality, renal recovery, and severity and duration of AKI in a small cohort of critically ill patients.…”
Section: Cell-cycle Arrest Biomarkers and Prognosismentioning
confidence: 99%